Nutrient digestibility and growth of five breeds of sheep under different levels of undegradable protein - Yulistiani D; Naufaliah N; Kardaya D; Subandriyo . (Jurnal Ilmu Ternak dan Veteriner, 2015)
A study was conducted to evaluate the effect of feeding different levels of rumen undegradable protein (UDP) in concentrate on performance of five breeds of sheep. Namely: Compass Agrinak (CA); Garut Composite breed (KG); Barbados Cross breed (BC); St Croix breed (SC); and Local Garut (GL) breed. Ten heads of sheep were used from each breed, in which each breed was grouped into 5 groups according to their body weight, and each sheep in each group was assigned to one of two treatments diet. The diet treatment consisted of concentrate containing different levels of undegradable protein (UDP). The levels of undegradable protein were 4.5% and 7.5%. Concentrate were formulated in iso nitrogen (CP content 16.7%) and iso energy (ME content 2.5 Mcal/kg). During feeding trial the sheep were kept in individual pen for three months. Study was conducted in randomized complete block design in factorial 5 x 2 arrangement, 5 levels of breeds sheep and 2 levels of UDP content. Results shows that there was no interaction effect of breed and levels UDP on feed consumption, average daily gain and feed conversion. These variables were significantly (P<0.05) affected by breed of sheep. The highest DMI (dry matter intake) was in KG sheep, the highest DMI caused by highest crude protein and gross energy intake, which in turn lead to highest average daily gain (ADG) of this breed. However the ADG of KG was not significantly different from GL. Apparent nutrient digestibility was not affected (P>0.05) by interaction between breed of sheep and UDP levels in the diet except for OM digestibility. While breed of sheep did not affect nutrient digestibility and UDP levels only affected NDF digestibility. From this study, it is concluded that increasing UDP in the diet did not improve growth performance of sheep. At similar quality of feed the growth performance was affected by breed of sheep in which KG and GL sheep had similar average daily gain (86.01 vs 82.38 g/day).